PBL dan Discovery Learning Berbantuan Virtual Laboratorium terhadap Keterampilan Pemecahan Masalah dan Efikasi Diri Siswa (JOEAI (Journal of Education and Instruction), 2026)
The purpose of this study was to test the effectiveness of the Problem-Based Learning (PBL) model, Virtual Lab-assisted Discovery Learning (DL), and the conventional model on improving problem-solving skills and self-efficacy. The research method used was a quasi-experimental design with a non-equivalent pre-test and post-test control group. The results showed a significant difference in improvement in problem-solving skills between the three groups (p < 0.001). The Virtual Lab-assisted Discovery Learning model provided the highest improvement (an average increase from 26.77 to 57.43), followed by the Virtual Lab-assisted PBL model (an average increase from 26.39 to 55.64) and the conventional model (an average increase from 27.48 to 34.45). Meanwhile, for the self-efficacy variable, although all classes experienced significant internal improvement (p < 0.05), no statistically significant difference was found between the groups (p = 0.741). In conclusion, the use of virtual laboratories in active learning models is effective for visualizing abstract concepts and for training students' systematic, logical thinking. However, self-efficacy growth tends to be evenly distributed across approaches that provide successful experiences.   Keywords: Discovery Learning, Self-Efficacy, Problem-Solving Skills, Problem-Based Learning, Virtual Laboratory